Learners’ Attitudes and Performance in Science Subjects in A-Level in Secondary Schools, in Mbarara, Uganda - AMIR, KABUNGA; Mohamed, Habiba C.; Mnjokava, Christina E. (IJRDO- Journal of Educational Research, 2016)
This research study aimed at investigating the learners’ attitudes and performance in science. The main objective of the study was to establish the relationship between learner’s attitudes and performance in science subjects based on age and gender. Cross-sectional research design was adopted for the study. Schools were randomly drawn from Mbarara district in Uganda. This gave a sample size of 300 form five and six secondary students. A questionnaire was used in collecting data for the study. The data was analyzed using SPSS to generate Pearson’s Chi Square test, Spearman Rank Correlation and bivariate to test the hypotheses of the study. The findings of the study revealed that attitude, age and gender had significant relationship with students’ performance in science subjects. Therefore, students’ attitudes should be very central to teachers, because affective dispositions are powerful predictors of students’ performance